Pengaruh Kompetensi dan Komitmen Organisasi terhadap Kinerja Guru dengan Motivasi sebagai Variabel Intervening pada Yayasan Murni Padang - Selvi Oktavia Azra Putri; M Fuan; Andre Ilyas (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to determine the effect of competence on motivation, the effect of organizational commitment on motivation, the effect of competence on teacher performance, and the effect of organizational commitment on teacher performance at the Murni Padang Foundation. The sample used in this research was the Teachers of the Murni Padang Foundation, Jl. Nipah No.33, Berok Nipah, West Padang, Padang City, West Sumatra. Totaling 40 respondents. The data collection methods used were library studies and field studies. The instruments of this research are observation and questionnaires. The data analysis method used is Structural Equation Model Partial Least (SEM-PLS) using SMART PLS 3.0 software. The results of this study indicate that there is a significant influence between competence on motivation, there is an insignificant influence between organizational commitment on motivation, there is a significant influence between competence on teacher performance, there is a significant influence between organizational commitment on teacher performance, there is a significant influence Between motivation and teacher performance, there is a significant influence between competence on teacher performance through motivation, there is an insignificant influence between organizational commitment on teacher performance through motivation.